Finland : Staff Report for the 2000 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2000)
Finland has recovered from the depression of the early 1990s, and is engaged in a new phase of economic expansion. Problems remain on the structural front and should be tackled for robust long-term growth. The restraint on the growth of public expenditures should be complemented by a significant reduction in the heavy tax burden on labor income. The macroeconomic policy stance should be complemented by other measures on the structural front to help expand the effective labor supply and enhance the supply response of the economy.